Post-operative complications after surgical management of scoliosis - Segundo Montero, Carlos; Meneses, David Alberto; Alvarado, Fernando; Godoy, Wilmer; Rosero, Diana Isabel; Ruiz, José Manuel; Silva, María Catalina; Roció Vargas, Jenniffer (Revista Colombiana de ortopedia y traumatología, 2020)
Background: The rate of complications in scoliosis surgery remains high. This study intends to determine the characteristics of the patients that are related to the presentation of perioperative complications, and to be able to use this information to take preventive measures. Material and Method: Descriptive cross-sectional retrospective study, including 230 patients and 318 procedures, was conducted on patients with scoliosis who underwent surgery to correct their deformity. Socio-demographic variables were evaluated using measures of central tendency measurements, followed by a bivariate analysis, and finally a multinomial logistic regression analysis. Results: A significance of P<.005 was found for diagnosis: neuromuscular and syndromic scoliosis presented with 28.8 and 16.66% of pneumonias, and a prevalence of 15.87 and 33.33% for pleural effusion, respectively. A urinary tract infection (1.88%) was observed in Congenital Scoliosis. A logistic regression model was performed, observing age as the main predictor for presenting with complications, and being more frequent in younger patients (P<.000). Discussion: It was found that more complications were present in younger patients. This outcome has not been previously reported, but can be used to support conservative behaviour in patients with early-onset scoliosis. The most common complication was pulmonary, with neuromuscular scoliosis being the diagnosis with more complications reported. These data are comparable with those in the literature, and should be taken into account when taking preventive measures and for the development of improvement plans. Evidence Level: IV